(untitled) (Swiss Medical Weekly, 2020)
AIM To assess the impact of the first wave of the COVID-19 pandemic on acute coronary syndromes and on the delay from symptom onset to first medical contact among patients presenting with ST-segment elevation myocardial infarction (STEMI), as well as to investigate whether there were patient-related reasons related to COVID-19 for delaying first medical contact. METHODS AND RESULTS All patients undergoing percutaneous coronary intervention (PCI) at the Geneva University Hospitals for acute coronary syndromes (ACS) during the first COVID-19 wave were compared with a control group consisting of all ACS patients who underwent PCI during the same period in 2019 and those treated in the period immediately preceding the pandemic. The primary outcome measure was the difference in the delay from symptom onset to first medical contact in the setting of STEMI between the COVID-19 period and the control period. Secondary outcome measures were the difference in ACS incidence and the impact of the COVID-19 pandemic on patients’ decisions to call the emergency services, assessed using a questionnaire. Delay from symptom onset to first medical contact was longer among patients suffering from STEMI in the COVID-19 period compared with the control period (112 min vs 60 min, p = 0.049). The incidence rate of ACS was lower during the COVID-19 period (incidence rate ratio 0.6, 95% confidence interval [CI] 0.449–0.905). ACS patients delayed their call to the emergency services mainly because of fear of contracting or spreading COVID-19 following hospital admission, as well as of adding burden to the healthcare system. CONCLUSION We observed prolonged delays from symptom onset to first medical contact and a decline in overall ACS incidence during the first wave of the COVID-19 pandemic, with a higher threshold to call for help among ACS patients.